The Effect of Oxytocin Massage on the Smoothness of Breast Milk Production in Postpartum Mothers - Sari, Ervina Maulia; Krismiyati, Murti; Putrianti, Berlina (Proceedings of the International Conference on Nursing and Health Sciences, 2024)
The smoothness of breast milk production is a key factor in achieving exclusive breastfeeding in Indonesia. Unfortunately, some mothers experience insufficient milk supply. This is often due to a lack of stimulation of the hormones oxytocin and prolactin, which play crucial roles in breast milk production. As a result, alternative interventions such as oxytocin massage are necessary. Objective to determine the effect of oxytocin massage on the smooth production of breast milk in postpartum mothers Mrs. N at PMB Tutik Purwani. This research employed an observational case study methodology. Primary data was collected from Mrs. N, who received oxytocin massage at PMB Tutik Purwani. The results indicated a significant difference in breast milk production before and after the oxytocin massage intervention. Babies of the participants experienced a weight gain of 300 grams. Oxytocin massage has a positive impact on breast milk production in postpartum mothers, leading to increased weight gain in their infants.